Effectiveness of Implementing General Principles of Good Government (AUPB) in Public Services - Sutrisno, Endang; Costa, Bruna; Silva, Pedro (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background: Public service quality is a crucial component of good governance, and the application of General Principles of Good Government (AUPB) plays a key role in ensuring effective public services. These principles, which include transparency, accountability, fairness, and efficiency, are essential for fostering trust between government institutions and citizens. However, there is a gap in understanding how effectively AUPB are implemented within public services and their impact on service delivery. Objective: This study aims to evaluate the effectiveness of implementing the General Principles of Good Government (AUPB) in public services. The research focuses on how these principles influence the efficiency, transparency, and quality of services provided by governmental institutions. Method: A mixed-methods approach was employed, combining qualitative interviews with public sector employees and quantitative surveys with citizens receiving public services. Data were collected from various government agencies to assess the practical application of AUPB principles and their impact on service quality. Results: The findings suggest that while AUPB are widely recognized, their implementation varies across institutions. Public services that effectively apply these principles show higher satisfaction rates among citizens, with increased accountability and transparency. Conclusion: The study concludes that implementing AUPB significantly improves the quality and transparency of public services, but challenges remain in ensuring consistent application across all governmental sectors.